Heterogeneity amongst GLP-1 RA cardiovascular outcome trials results - Melo, Miguel (2021)
Funding Information: MM participated in advisory board meetings and received speaker’s fees from the following companies: AstraZeneca, Bial, Boeringher-Ingelheim, Lilly, NovoNordisk and Sanofi. CG reports consulting and speaking fees from Astrazeneca, Novo Nordisk, Lilly, Boheringer Ingelheim, MSD and Bayer. JSN reports receiving research funding from AstraZeneca, and Merck sa; and consulting/speaker’s fees from Abbott, AstraZeneca, Bial, Boehringer Ingelheim, Janssen, Lilly, Medinfar, Merck sa, Merck Sharp & Dohme, Mundipharma, Novartis, Novo Nordisk, Roche, Sanofi, Servier, Tecnimede. LA reports membership of advisory board, consultancy/ speaker's fees from: Astra-Zeneca, Lilly, Bhoeringer, NovoNordisk and Bial.DC is member of Advisory Boards of Novo-Nordisk, Astra-Zeneca, Eli Lilly, Sanofi-Aventis and is speaker for Novo-Nordisk, Astra-Zeneca, Eli Lilly. Publisher Copyright: © 2021, The Author(s).